The protective role of employment in depression: insights from 2005 to 2018 NHANES information - Li, Fang; Chu, Zheng (Frontiers in Psychiatry, 2024)
BackgroundDepression is closely associated with employment status, which serves as a complex social determinant. This study explores the relationship between employment status and depression.MethodsData from the National Health and Nutrition Examination Survey (NHANES) spanning 2005 to 2018 were analyzed. The study included 29,452 participants aged 20 and older with complete data on employment and depression. Logistic regression models were applied to examine the association between employment and depression, adjusting for covariates such as age, gender, ethnicity, marital status, education, poverty-to-income ratio (PIR), BMI, diabetes, hypertension, smoking, and alcohol status.ResultsThe study revealed an overall depression prevalence of 8.61%, with significant variation across employment statuses—non-employed (11.77%), part-time (6.58%), and full-time (4.52%) workers. Employed individuals, particularly those in the 40-59 age group and with lower PIRs, showed reduced odds of depression (OR 0.42, 95% CI: 0.36–0.48, p=0.000). Stratified analyses confirmed lower depression odds for employed individuals regardless of gender or marital status.ConclusionEmployment status has a significant impact on depression risk, with full-time work showing the strongest protective effect against depressive symptoms. The study underscores the role of sociodemographic factors in depression and highlights the need for policies promoting stable employment and mental health support, especially for economically vulnerable groups.